Usulan Penerapan Total Productive Maintenance pada Transfer Conveyor 17A - Sahrupi, Sahrupi; Juriantoro, Juriantoro (Universitas Serang Raya, 2018)
The quantity and quality of coal affects the efficiency of the generating unit, therefore the utilization of Transfer Conveyor 17A is very necessary to fulfill the fuel requirement (coal) of PT Indonesia Power Unit Generation Unit Suralaya. Transfer conveyor is an additional element in a conveyor belt circuit that serves to channel coal from unloading area until coal bunker (power plant). This study aims to find out the value of OEE Transfer Conveyor 17A which is used as the basis of proposed improvement based on the lowest value of the three parameters in OEE. The concept of research adopting OEE method with the value of quality is assumed 97,50% because the equipment that becomes the object of research does not produce the product. The result of calculation obtained by OEE value equal to 82,98% with ratio Availability 86,76% Performance Eficiency 98,09% and Rate of Quality 97,50%. A planned maintenance action is required to avoid unpredictable engine damage such as the operator checking the machine before it is operated, providing periodic training to operators and maintenance to improve their capabilities.